A dynamic analysis on public bus transport’s supply quality by using AHP - Duleba, Szabolcs; Mishina, Tsutomu; Shimazaki, Yoshiaki (Transport, 2012)
Nowadays, it is a really important issue to improve the supply quality of city public bus transportation in many cases. Meanwhile, the different participants of transport systems have different ideas on the ways of improvement, for this reason the taken measures can be inefficient and expensive. The operational costs are steadily increasing (e.g. price of fuel, wages, etc.) therefore the decision makers do not really have the opportunity to lower the price of tickets. For solving the above mentioned problems, before creating a plan of improving a certain public system, a clear image should have been gained on the preferences of passengers, company managers and governmental decision makers. In the current paper a general three-level-hierarchical model has been set up to analyze dynamically the public bus transport system of a city. The price is excluded, only the elements of supply quality are assessed in the hierarchy. Based on the model, questionnaires were created and for the analysis, Analytic Hierarchy Process (AHP) was used to determine preference weights of evaluators from different evaluator groups. Passengers, company managers and governmental officers evaluated exactly the same type of questionnaires so the results are comparable. Avoiding the difficulties of other AHP applications, we used a simplified Saaty-scale for scoring so that the missing data of the matrices could be calculated by an algorithm as well. This study revealed a priority ranking of the elements of supply quality within each level, and this ranking is comparable among the participants of public bus system. This may help the policy makers to synthesize various aspects of public transportation. First Published Online: 19 Sep 2012